Converting waste into Sustainable Aviation Fuel (SAF): A systematic literature review - Sabah Mariyam (14150859) (2025)
The global aviation sector is essential for connecting people, cultures, and economies, but it significantly contributes to greenhouse gases (GHG), exacerbating environmental concerns. This systematic literature review examines the transformation of waste into Sustainable Aviation Fuels (SAF), highlighting their potential to reduce the aviation industry's carbon footprint. The review explores waste-to-fuel technologies, such as gasification, pyrolysis, liquefaction, and Fischer-Tropsch synthesis, mainly focusing on the eight ASTM-certified bio-jet fuel production pathways, demonstrating the highest readiness levels. The study covers methodologies, case studies, and optimszation studies, identifying significant trends, advancements, and gaps in the literature to develop SAF from waste. Key findings reveal that some processes can significantly reduce CO2 emissions and improve sustainability, but challenges persist. Despite the potential of thermochemical pathways combined with oil hydro-processing and their technological readiness, the pathway's production costs remain high, and robust regulatory support is needed to scale up SAF production. Integrating pathways in a hybrid format could further offer a synergistic approach to developing SAF that combine high performance with economic and environmental sustainability. Future research should address these gaps, enhance energy and economic efficiencies, and explore innovative feedstocks and catalytic processes. The review provides valuable insights for environmentalists, industry stakeholders, engineers, and policymakers, supporting efforts to achieve sustainable aviation and global environmental goals. Other Information Published in: Renewable and Sustainable Energy Reviews License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.rser.2025.116380